CEUS in hepatocellular carcinoma and intrahepatic cholangiocellular carcinoma in 320 patients - early or late washout matters: a subanalysis of the DEGUM multicenter trial - Wildner, Dane; Bernatik, T.; Greis, C.; Seitz, K.; Neurath, Markus; Strobel, Deike (Ultraschall in der Medizin, 2015)
The aim of the study was the comparison of tumor vascularization and contrast enhancement in contrast-enhanced ultrasound (CEUS) for the characterization of hepatocellular carcinoma (HCC) and intrahepatic cholangiocellular carcinoma (ICC). We present data of the subpopulations HCC and ICC examined in the DEGUM multicenter trial for the characterization of focal liver lesions in clinical practice.Based on the data of the DEGUM multicenter trial (1349 patients), all patients with histologically proven HCC (n = 278) and ICC (n = 42) were analyzed. The vascularity pattern and contrast enhancement pattern during the arterial, portal-venous and late phase were compared.An underlying liver cirrhosis was found in 214/278 patients with HCC (76.9 %) and 7/42 patients with ICC (16.7 %). In CEUS, HCC showed a global arterial hyperenhancement compared to ICC (HCC: tumor center: 60.3 %; tumor periphery: 75 %; ICC: tumor center: 16.7 %; tumor periphery: 40.5 %). ICC showed an initial contrast enhancement primarily at the tumor periphery (ICC: 85.7 % vs. HCC: 61 %) followed by an early portal-venous contrast washout in the tumor center (ICC: 85.8 % vs. HCC: 49.8 %) and tumor periphery (ICC: 66.7 % vs. HCC: 32.6 %). HCC showed a delayed contrast washout (late phase hypoenhancement: HCC: 75 % vs. ICC: 92.9 %).ICCs are rare in cirrhotic livers. CEUS can demonstrate differences in the vascularization patterns between HCC and ICC. HCC showed an arterial global hyperenhancement and delayed contrast washout in the late phase. ICCs are characterized by an arterial contrast enhancement at the tumor periphery with early contrast washout of the vascularized parts of the lesions in the portal-venous and late phase.
EVALuna2:1988